Reflections on Spirituality and Health. - Wright, Stephen (John Wiley & Sons, 2007)
This is a scholarly exploration of the subject of spirituality and health and is relevant to all health care practitioners and those who support them. Drawing on the author' s rich personal experience in the field, his previously published material on the subject in professional journals and a wide range of research and other relevant literature, the book explores a diverse range of themes relevant to the everyday work of the health care practitioner. Is spirituality of any relevance to the work of carers? How is it best integrated? How do we address the spiritual needs of health care staff? W.